Antihyperuricemia Activity Test of Tempuyung Leaf Infusion (Sonchus arvensis L.) on Male Swiss Webster Mice (Mus musculus) - Estevany Priliansi; Sarah Puspita Atmaja; Ari Widhiarso (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Treatment of hyperuricemia with allopurinol has a risk of hypersensitivity reactions that can be fatal with mortality rates reaching 20%-25%. As an alternative, tempuyung leaves (Sonchus arvensis L.) are known to contain flavonoids that have the potential to reduce uric acid levels. Objectives: To identify chemical compounds and evaluate their effects as antihyperuricemia. Methodology: A laboratory experimental study conducted for 14 days using male mice. The mice were divided into several groups, namely the negative control (Na-CMC 0.5%), positive control (allopurinol), and groups treated with Sonchus arvensis leaf infusion at doses of 50 mg/kg BW, 100 mg/kg BW, and 150 mg/kg BW. Hyperuricemia induction was performed for 7 days using potassium oxonate and chicken liver juice. Uric acid levels were measured using an enzymatic method with a UV-Vis spectrophotometer. Data analysis was performed using Paired T-Test and One-Way ANOVA statistical tests. Result: The infusion of Sonchus arvensis L. leaves indicates the presence of flavonoids, alkaloids, saponins, and tannins. The highest uric acid-lowering effect appears at a dose of 150 mg/kg BW, with a reduction of 26.517%. All doses of the infusion show a significant decrease in uric acid levels, both after hyperuricemia induction and on days 7 and 14 of treatment. A significant difference in uric acid reduction between groups appears at doses of 50 mg/kg BW and 100 mg/kg BW, while the dose of 150 mg/kg BW does not show a significant difference.